1999
DOI: 10.1093/oxfordjournals.schbul.a033374
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Atypical Antipsychotic Drugs on Neurocognitive Impairment in Schizophrenia: A Review and Meta-analysis

Abstract: Cognitive deficits are a fundamental feature of the psychopathology of schizophrenia. Yet the effect of treatment on this dimension of the illness has been unclear. Atypical antipsychotic medications have been reported to reduce the neurocognitive impairment associated with schizophrenia. However, studies of the pattern and degree of cognitive improvement with these compounds have been methodologically limited and have produced variable results, and few findings have been replicated. To clarify our understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
307
2
21

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 637 publications
(340 citation statements)
references
References 104 publications
10
307
2
21
Order By: Relevance
“…Effect sizes of measured change ranged from small to medium for both tests and domain scores in each battery (see Table 2). This was consistent with modest effect sizes for neuropsychological change reported in metaanalytic studies and larger multisite studies (Harvey et al, 2000;Johnson-Selfridge and Zalewski, 2001;Keefe et al, 1999;Woodward et al, 2005).…”
Section: Sensitivity To Changesupporting
confidence: 77%
See 1 more Smart Citation
“…Effect sizes of measured change ranged from small to medium for both tests and domain scores in each battery (see Table 2). This was consistent with modest effect sizes for neuropsychological change reported in metaanalytic studies and larger multisite studies (Harvey et al, 2000;Johnson-Selfridge and Zalewski, 2001;Keefe et al, 1999;Woodward et al, 2005).…”
Section: Sensitivity To Changesupporting
confidence: 77%
“…Evaluation of the procognitive effects of atypical relative to typical antipsychotics has indicated somewhat greater benefit with atypical compared with typical antipsychotics (Bilder et al, 2002;Green et al, 2002;Harvey et al, 2000;Keefe et al, 1999;Purdon et al, 2000). In general, modest cognitive benefits from antipsychotic medications are characterized by reduction of generalized cognitive deficits across a wide range of abilities, rather than particular effects on a specific neuropsychological domain (Buchanan et al, 1994;Cassens et al, 1990;Hill et al, 2004a;Rollnik et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several years, studies have shown significantly improved cognitive performance in schizophrenic patients taking novel antipsychotics in comparison to those taking high-potency classical antipsychotics or no treatment (Bilder et al, 2002;Purdon et al, 2000;Keefe, Silva, Perkins, & Lieberman, 1999). In one study, investigators found that switching patients from classical to novel antipsychotics improved cognitive functioning (Mori, Nagao, Yamashita, Morinobu, & Yamawaki, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment has considerable detrimental effects on the social and vocational outcomes of schizophrenia patients, with the severity of impairment being closely related to the severity of community and work disability (Green, 1996;Green et al, 2004). To date, studies with first-and second-generation antipsychotic drugs have been unable to demonstrate consistently marked effects on cognitive function in schizophrenic patients (Harvey and Keefe, 2001;Keefe et al, 1999Keefe et al, , 2007Woodward et al, 2005), resulting in an increased emphasis on testing other agents for efficacy in cognitive enhancement.…”
Section: Introductionmentioning
confidence: 99%